"Targeting or supporting, what drives patterns of aggressive intervention in fights?". Issue 2 (8th November 2015) - Puga‐Gonzalez, Ivan; Cooper, Matthew A.; Hemelrijk, Charlotte K.
Abstract : GrooFiWorld is an individual‐based, computational model of social interactions that can be used to examine factors underlying reciprocation and interchange of social behavior in primate societies. Individuals within GrooFiWorld are programed to maintain spatial proximity and thereby form a group. When an individual encounters another individual in its proximity, the individual attacks the other if the risk of losing is low. Otherwise, the individual considers grooming the other. Patterns of social behavior that emerge in the model resemble empirical data from primates. Triadic aggression emerges when an individual attacks one of the former combatants by chance immediately after an aggressive interaction, and reciprocation and interchange of grooming and support emerge even though individuals have no intention to help others or pay back services. The model generates predictions for patterns of contra‐intervention that are counterintuitive within a framework of interchange of social services, such as that individuals receive more contra‐intervention from those whom they groom more frequently. Here we tested these predictions in data collected on social interactions in a group of bonnet macaques ( Macaca radiata ). We confirmed the predictions of the model in the sense that contra‐intervention was strongly correlated with dyadic aggression which suggests that contra‐intervention is a subset of dyadic aggression. Adult females directed more contra‐intervention to those individuals from whom they received more grooming. Further, contra‐intervention was directed down the dominance hierarchy such that adult females received more contra‐intervention from higher ranking females. Because these findings are consistent with the predictions from the GrooFiWorld model, they suggest that the distribution of interventions in fights is regulated by factors such as dominance rank and spatial structure rather than a motivation to help others and interchange social services. Am. J. Primatol. 78:247–255, 2016. © 2015 Wiley Periodicals, Inc.